Identifikasi Potensi dan Status Pengembangan Desa Wisata di Kabupaten Lombok Tengah, Nusa Tenggara Barat - Azhar Amir; Taufan Daniarta Sukarno; Fauzi Rahmawati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2020)
Identifying Potential and Development Status of Tourism Village Development in Central Lombok Regency, West Nusa Tenggara Tourism village is a combination between natural attraction, culture, and local community creativity, supported by accommodation and other facilities that can attract tourists to visit. Central Lombok Regency is one of the regions that have many potential of tourism villages that yet to be developed. Its location is considered to be strategic and supported by the Special Economic Region (KEK) of Mandalika as government’s super-priority destination. Tourism villages can be an alternative destination to support grand tourism project in Mandalika. The current problem is there is lack of information on tourism villages in Central Lombok Regency. This study aims to identify tourism village development potentials and classify the development status of tourism village in Central Lombok Regency. This research used mix-method approaches. Data collection used primary and secondary sources. Data were gained from interview, observation, questionnaire, and literature study. Data were analyzed using descriptive method, through scoring and classifying tourism village statuses. Result of this study shows that attraction and accessibility were the most important aspects to support tourism village development with scoring value of 3.1 and 3.3 respectively. Amenity, community readiness, and administrator had scoring value below 3. Village-owned enterprise (BUMDesa) and tourism awareness groups (Pokdarwis) are yet to support tourism village development. There are lack of promotions, thus needs to be supported by local government and agencies. Most of the villages in Central Lombok Regency were categorized as pioneer and developed. Only Sade village and Ende village were categorized as advanced, with main attraction of Sasak cultural heritage which was established several decades ago.